High School Students' Mathematical Communication Skills Through Ethnomatematics-Based Realistic Mathematics Learning Approaches in Geometry Transformation Materials - Khusnul Hotimah; Isnawati Lujeng Lestari (Noumerico: Journal of Technology in Mathematics Education, 2023)
Mathematical communication ability is the ability of students to use mathematics as a form of communication (the language of mathematics) and student's ability to convey the mathematics they learn as the content of the message to be conveyed. This study aims to describe the Mathematical Communication Skills of High School Students Through an Ethnomatematics-Based Realistic Mathematics Learning Approach on Geometry Transformation Materials. This research is a type of descriptive research with a qualitative approach. The selection of subjects used in this study used an interpersonal intelligence questionnaire, which involved all students of class XI IIS 3 State Islamic High School 1 Pasuruan. Based on the interpersonal intelligence questionnaire scores, three subjects were selected with high, medium, and low levels of interpersonal intelligence. Then, these three subjects will examine the student's ability to draw the correct solution, explain the answer systematically, and construct a problem into a mathematical model. The results of this study indicate that the mathematical communication skills of students with high, medium, and low levels of interpersonal intelligence have many differences in problem-solving on the questions given